Improved Sugar Production by Optimizing Planetary Mill Pretreatment and Enzyme Hydrolysis Process. (11th October 2015) - Kwon, Jeong Heo; Lee, Siseon; Lee, Jae-Won; Hong, Youn-Woo; Chang, Jeong Ho; Sung, Daekyung; Kim, Sung Hyun; Sang, Byoung-In; Mitchell, Robert J.; Lee, Jin Hyung
Abstract : This paper describes an optimization of planetary mill pretreatment and saccharification processes for improving biosugar production. Pitch pine ( Pinus rigida ) wood sawdust waste was used as biomass feedstock and the process parameters optimized in this study were the buffering media, the milling time, the enzyme quantity, and the incubation time. Glucose yields were improved when acetate buffer was used rather than citrate buffer. Initially, with each process variable tests, the optimal values were 100 minutes of milling, an enzyme concentration of 16 FPU/g-biomass, and a 12-hour enzymatic hydrolysis. Typically, interactions between these experimental conditions and their effects on glucose production were next investigated using RSM. Glucose yields from the Pinus rigida waste exceeded 80% with several of the conditions tested, demonstrating that milling can be used to obtain high levels of glucose bioconversion from woody biomass for biorefinery purposes.